Mind Your Learner's Mind: A Cognitive Approach to Teaching Phrasal Verbs - Geld, Renata; Stanojević, Mateusz-Milan (2004)
Cognitive linguistics claims that our knowledge of the language is intimately connected with our general cognitive abilities (Langacker 1987, Lakoff and Johnson 1999). This statement has a profound influence on the theory of language structure and processing. According to the cognitive view all language is symbolic in nature, which in turn implies that every unit, no matter how schematic, has meaning (Langacker 1987). These units are combined into larger structures of varying conventionality. In order for the integration to be successful, accommodation needs to take place (Langacker 1987:73-76). Based on the human ability of metaphorical thought (Lakoff and Johnson 1980, Lakoff and Johnson 1999), semantic accommodation may involve the extension of meaning from a physical into an abstract conceptual space (see Fauconnier 1994, Gärdenfors 2000) . Our research represents an attempt to determine to what extent the students of English as well as English teachers provide for the primacy of meaning and metaphorical extension when faced with the task of learning/teaching phrasal verbs. The research has two parts. In the first part, the students will be asked to describe activities they believe would facilitate the learning process. Our primary claim is that despite no or very little formal training in cognitive linguistics, the learners will recognize the primacy of meaning as the foundation for developing a number of relevant learning strategies that fall within the category of memory, cognitive and compensation strategies (Oxford 1990). Furthermore, we believe that the students’ activities will reflect their awareness of the importance of metaphor in construing the meaning of the verbs. In the second part of the research we are going to focus on teachers. We claim that very few teachers will explicitly take into account metaphorical extension. Finally, the same group of teachers will be asked to evaluate activities designed in such a way as to take into account both the primacy of meaning and metaphorical extension. Based on our results we will discuss the teacher attitude towards instruction based on the principles of cognitive linguistics, and the feasibility of applying cognitive linguistics in class.
Projekt MZOS
ENG